2018
DOI: 10.1080/09540962.2018.1556004
|View full text |Cite
|
Sign up to set email alerts
|

Public service motivation and performance: The role of organizational identification

Abstract: Although the association between public service motivation (PSM) and job performance has received increased attention, there is limited knowledge of the mechanisms underlying its effects. Utilizing data from Chinese civil servants and their supervisors, the authors found that PSM results in higher levels of organizational identification and leads to higher levels of job performance because civil servants perceive the organization's fate and results as their own. IMPACT Our study demonstrates that organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 52 publications
4
54
0
4
Order By: Relevance
“…Also, the Chinese culture emphasises guanxi and personal favour (Xin & Pearce, ), which could result in high response rate in surveys (Bui, Zeng, & Higgs, ). For example, similar or even higher response rate was reported in other studies conducted in China, such as 83% (Schwarz, Newman, Cooper, & Eva, ), 82% (Miao, Eva, Newman, & Schwarz, ), 93% (Liu, Luksyte, Zhou, Shi, & Wang, ), and 95% (Wang, Xu, Sun, & Liu, ). For these reasons, although the response rate is high, we do not consider it as unduly problematic.…”
Section: Methodssupporting
confidence: 80%
“…Also, the Chinese culture emphasises guanxi and personal favour (Xin & Pearce, ), which could result in high response rate in surveys (Bui, Zeng, & Higgs, ). For example, similar or even higher response rate was reported in other studies conducted in China, such as 83% (Schwarz, Newman, Cooper, & Eva, ), 82% (Miao, Eva, Newman, & Schwarz, ), 93% (Liu, Luksyte, Zhou, Shi, & Wang, ), and 95% (Wang, Xu, Sun, & Liu, ). For these reasons, although the response rate is high, we do not consider it as unduly problematic.…”
Section: Methodssupporting
confidence: 80%
“…This will allow the evaluation of the extent to which stereotypes are broadly shared and deviation from general stereotypical beliefs. Moreover, as institutional logics, cultures and perceptions of the public sector and its employees are very diverse across countries, the results of this study are hard to generalize to other countries (Miao et al 2019). In addition, the motivation of people to work in the public sector might also be very different across countries (Kim et al 2013;Miao et al 2019).…”
Section: Limitations and Further Researchmentioning
confidence: 85%
“…Given these results concerning motivational factors and organizational commitment, organizations should focus on devoting attention to the relationship between increased motivation and increased productivity. Miao et al (2019) found that although a link between public service motivation (PSM) and work performance in cases of increased attention was found, there is limited knowledge of the underlying mechanisms causing these effects. Using data from Chinese civil servants and supervisors, the authors have found that PSM leads to improved performance and organizational identification, as civil servants consider the organization's results to be important.…”
Section: Theoretical Backgroundmentioning
confidence: 99%